Permissivités des grands topoï romanesques dans l’œuvre de Boualem Sansal - Romain, Lisa (Romanica Silesiana, 2021)
Being an author whose main struggle has been to track down relentlessly ready-for-use thought structures, the use of literary topoï is far from being self-evident for Boualem Sansal. That’s why the appearance of a topos in his novels is always the sign of a thoughtful aesthetic and ethic choice. Thus, great literary topoï of 17th and 18th centuries novels embodies, in his mind, the golden age of a fully potent fiction. Dealing with a harsh reality and expected to complete french readership expectations of documentary sources, Boualem Sansal’s work constantly intends to reassert the role of a fiction that has been too much tamed, for him, in modern literary aesthetics. That’s the way we can understand his occasional but meaningful use of topoï.